TABIR SURYA VS IKLIM TROPIS: tabir surya, sunscreen, ultra violet, tropis, iklim - Ria Andriani Mukti (Buana Pendidikan, 2014)
The presence of ultraviolet (UV) filter in skincare and cosmetic products represents a key benefit that cosmetics can provide consumers. The hazards of UV light exposure are well known. It is estimated that the incidence of nonmelanoma skin cancer in United States exceeds one million cases per year. UV induced or photoaging accounts for 80 % - 90 % of visible skin aging. UV radiation damages the skin by both direct effects on DNA and indirectly on the skinÃ‚â€™s immune system. The regular use of sunscreens has been shown to reduce the number of actinic or precancerous keratosis and solar elastosis. Sunscreen also prevents immunosupression. The cosmetic formulator has expanding menu of active sunscreen ingredients for incorporation into a variety of cosmetic formulation.